ANALISIS PREFERENSI MASYARAKAT TERHADAP BUS TRANS PADANG - Rusy Dina; Akhirmen Akhirmen; Novya Zulva Riani (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2016)
This research aims to analyze the effect of: respondents income,services quality, private vehicle ownership, and tarrifs of Trans Padang to preference of societies to  Bus Trans Padang. This type of research is descriptive and associative. Data in this research are primary data, taken at August 2015. The data collection technique is by distributing questionnaires and direct observation. Population in this research is all users of transport services Trans Padang, by taking a sample of 100 respondents. Inductive analysis in this research include: multiple linear regression analysis; Multicolinearity test;  Heteroskedastisitas test; The coefficient of determination; t test; and F test. The results showed that respondents income  and ownership of two-wheeled vehicle does not significantly influence people's preferences of Bus Trans Padang. As for the quality of service and tariff Trans Padang significant effect on people's preferences of Bus Trans Padang. In collectively respondents income, services quality,the ownership of  two-wheeled vehicle, and tariff Trans Padang have significant influence to  preferences of societies to Bus Trans Padang.  Keywords: Preference, income, quality of service, the two-wheeled personal vehicle ownership, tariff Trans Padang.